A case series of an off-the-shelf online health resource with integrated nurse coaching to support self-management in COPD - Early F; Young JS; Robinshaw E; Mi EZ; Mi EZ; Fuld JP (International Journal of COPD, 2017)
Frances Early,1 Jane S Young,2 Elizabeth Robinshaw,3 Emma Z Mi,4 Ella Z Mi,4 Jonathan P Fuld1 1Centre for Self Management Support, Cambridge University Hospitals NHS Foundation Trust, Cambridge, UK; 2Faculty of Health, Social Care and Education, School of Nursing and Midwifery, Anglia Ruskin University, Cambridge, UK; 3Gloucestershire Hospitals NHS Foundation Trust, Gloucester, UK; 4School of Clinical Medicine, University of Cambridge, Cambridge, UK Background: COPD has significant psychosocial impact. Self-management support improves quality of life, but programs are not universally available. IT-based self-management interventions can provide home-based support, but have mixed results. We conducted a case series of an off-the-shelf Internet-based health-promotion program, The Preventive Plan (TPP), coupled with nurse-coach support, which aimed to increase patient activation and provide self-management benefits. Materials and methods: A total of 19 COPD patients were recruited, and 14 completed 3-month follow-up in two groups: groups 1 and 2 with more and less advanced COPD, respectively. Change in patient activation was determined with paired t-tests and Wilcoxon signed-rank tests. Benefits and user experience were explored in semistructured interviews, analyzed thematically. Results: Only group 1 improved significantly in activation, from a lower baseline than group 2; group 1 also improved significantly in mastery and anxiety. Both groups felt significantly more informed about COPD and reported physical functioning improvements. Group 1 reported improvements in mood and confidence. Overall, group 2 reported fewer benefits than group 1. Both groups valued nurse-coach support; for group 1, it was more important than TPP in building confidence to self-manage. The design of TPP and lack of motivation to use IT were barriers to use, but disease severity and poor IT skills were not. Discussion: Our findings demonstrate the feasibility of combining nurse-coach support aligned to an Internet-based health resource, TPP, in COPD and provide learning about the challenges of such an approach and the importance of the nurse-coach role. Keywords: COPD, self-management, Internet, coaching, patient activation